Efficacy and Safety of Suprachoroidal Triamcinolone Acetonide in Cases of Resistant Diabetic Macular Edema - Jamil, Muhammad Itban; Ahmed, Najam Iqbal; Ashraf, Bushra; Afzal, Sohaib; Javed, Maham; Qayum, Abdul (Biological and Clinical Sciences Research Journal, 2025)
Diabetic macular edema (DME) in people with diabetes often resists standard treatments. Suprachoroidal triamcinolone acetonide injections target therapy, potentially improving outcomes with fewer side effects. This study aims to advance understanding of its efficacy and safety in managing DME, adding to the limited literature. Objective: To evaluate the safety and effectiveness of SCTA injection in patients with resistant diabetic macular edema. Methods: The study was conducted at the Department of Ophthalmology, Sir Ganga Ram Hospital, Lahore. The study duration was 6 months from 5th June 2024 to Dec 5th 2024. After approval, 30 patients with resistant DME and meeting the inclusion criteria were enrolled in the study after taking informed written consent. A special technique was used to administer suprachoroidal triamcinolone acetonide. Patient follow-up was done at 1 month and 3 months after treatment to measure change in study variables from the baseline. Results: The study involved 30 participants. Mean logMAR BCVA decreased significantly at 1 month (0.56±0.053) and 3 months (0.42±0.072) from baseline (0.83±0.048), p=0.000. Mean CMT at 1 and 3 months was significantly lower than baseline, p=0.000, with a significant decrease between these periods. Mean IOP was significantly higher at 1 month (13.80±1.65 mmHg, p=0.000) compared to baseline (12.43±1.63 mmHg), and was insignificantly higher at 3 months (12.6±1.63 mmHg, p=0.056). Conclusion: Our study highlights suprachoroidal triamcinolone acetonide’s efficacy in treating refractory diabetic macular edema, showing significant visual acuity improvement and central macular thickness reduction. Transient intraocular pressure increases were observed but reverted to baseline, affirming treatment safety and effectiveness.